THE CONCEPT OF CITIZENSHIP IN ISLAMIC POINT OF VIEW - Hadi, Abdul (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The history of nations has witnessed how movements advocating separatism or religious extremism pose challenges to state security and unity, particularly in diverse societies. This issue remains a significant challenge for developing countries today. This study explores the concept of citizenship from an Islamic perspective, drawing from primary Islamic sources such as the Qur'an, the Sunnah of the Prophet Muhammad (peace be upon him), and historical precedents from his leadership. Employing qualitative library research, data was collected through textual analysis of Islamic scriptures and historical records. The study categorizes key aspects of Islamic citizenship and employs descriptive analysis to examine its moral, social, and political dimensions. Findings reveal that Islamic citizenship is centered on justice, social harmony, welfare, and state defense—offering a framework distinct from Western notions of citizenship. Rather than being confined to administrative rights, Islamic citizenship embodies active contributions to societal welfare, security, and global humanitarian efforts. Ultimately, this study concludes that the Islamic perspective on citizenship prioritizes collective welfare and national stability, transcending mere legal documentation and emphasizing broader moral and societal obligations.